Study effectiveness of tamsulosin in the management of lower third ureteral stones with size 1cm or less - عوكان, مجدي; لؤي نداف; أيمن حرفوش (Latakia University Journal -Medical Sciences Series, 2024)
Background: Ureteral stones are a common problem in daily emergency department practice, and medical therapy may be offered to facilitate stone expulsion in patients with distal ureteral calculi. Aim: The purpose of this study was to evaluate the effectiveness of tamsulosin in management of lower ureteric stones with size 1 cm or less. Materials and Methods: This was an analytical comparative study (prospective) included 142 patients with stones in the lower third of ureter at Tishreen University Hospital- Lattakia-Syria during one year period (2023- 2024). Patients were divided into two groups according to the method of management: group 1 included 71 patients who received treatment with tamsulosin and group 2 included 71 patients who didn't receive any therapy, in which final outcome were compared between two groups. Results: A total of 142 patients, 101 males (71.1%) and 41 females (28.9%) with a mean age of 37.66±14.6 years were included in the study. The stones were solitary in in 95.8%, multiple in 4.2% with stone sizes less than 5 mm in 63 cases(44.4%). There were no significant differences between two groups regarding of age(p:0.6), sex(p:0.3), number of stones(p:0.6), and its size(p:0.2). The success rate of stone expulsion was higher in tamsulosin group but without significant difference(87.3% versus 78.9%,p:.0.09). There were no significant correlation between size of stones and the rate of success in the two groups(p:0.07). In addition to, mean duration of stones passage was significantly shorter in tamsulosin group(7.66±2.4 days versus 10.6±3.3 in placebo,p:0.01). Conclusion: The current study demonstrated that tamsulosin provides better stone expulsion in the cases of distal ureterolithiasis without significant difference compared with placebo, but with minimum amount of time.